The relationship of somatization with fatigue and exhaustion as chief complaints - CÖBEK ÜNALAN, GÜLRU PEMRA (My University, 2020)
Background
Keywords: TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Somatization; medically unexplained symptoms; PHQ-SADS; MEDICALLY UNEXPLAINED SYMPTOMS; PRIMARY-CARE; SOMATOFORM DISORDERS; GENERAL-PRACTICE; PHYSICAL SYMPTOMS; PREVALENCE; ANXIETY; CLASSIFICATION; DEPRESSION; VALIDATION